A Perspective toward Practical Lithium–Sulfur Batteries - Zhao, Meng; Li, Bo-Quan; Zhang, Xue-Qiang; Huang, Jia-Qi; Zhang, Qiang (ACS central science, 2020)
Lithium–sulfur (Li–S) batteries have long been expected to be a promising high-energy-density secondary battery system since their first prototype in the 1960s. During the past decade, great progress has been achieved in promoting the performances of Li–S batteries by addressing the challenges at the laboratory-level model systems. With growing attention paid to the application of Li–S batteries, new challenges at practical cell scales emerge as the bottleneck. In this Outlook, the key parameters for practical Li–S batteries to achieve practical high energy density are emphasized regarding high-sulfur-loading cathodes, lean electrolytes, and limited excess anodes. Subsequently, the key scientific problems are redefined in practical Li–S batteries beyond the previous ones under ideal conditions. Finally, viable strategies are proposed to address the above challenges as future research directions.